The Communicativeness and Critical Thinking Devices of Language Supplementary Materials for Primary School: Piranti Berpikir Kritis dan Komunikatif Materi Penunjang Kebahasaan di Sekolah Dasar - Rohmani Nur Indah; Galuh Nur Rohmah (RETORIKA: Jurnal Ilmu Bahasa, 2020)
Studies show that teaching materials can be integrated with critical thinking skills for enhancing successful learning. However, the integration is not always clear as the communicativeness aspect of the materials also contributes to the goal of effective learning. This study focuses on critical thinking devices and the aspect of communicativeness fulfilled or violated in Indonesian primary school supplementary materials for language courses. It employs content or document analysis on the supplementary materials of the first graders on courses of English, Indonesian and Javanese languages. The analysis is based on the assumption that critical thinking tools and communicative aspects are the two main pillars that characterize the quality of language teaching materials in elementary schools. In addition, critical thinking tools are linked with communicative aspects of language teaching materials to target targeted competency standards. The results show that the communicativeness aspect is supported by the use of real context and authenticity of the materials. In terms of critical thinking device, the supplementary materials are supported by clear purpose in presenting key information. The evaluation on the supplementary materials concerns with the effort to improve the quality of primary school student’s cognitive attainment and critical thinking through communicative supplementary materials.